Heart Disease Knowledge Questionnaire: Psychometric Properties in Brazilian Adults - Lima, Fernanda Maria Alves [UNESP]; Jamas, Milena Temer [UNESP]; Miot, Hélio Amante [UNESP]; Garcia de Avila, Marla Andréia [UNESP] (Taylor & Francis, 2022)
Background: The assessment of knowledge about cardiovascular diseases through instruments helps to identify gaps and educational needs of the target audience. Purpose: To validate and verify the psychometric properties of the Brazilian version of the Heart Disease Knowledge Questionnaire (HDKQ-BR) for adults in Brazil. Methods: Cross-sectional methodological study carried out in a Brazilian city with 300 participants. Internal consistency, temporal stability (test-retest) and convergent structural validity were verified. Item Response Theory (IRT) was used to determine parameters a (discrimination) and b (difficulty) of each item and the unidimensionality of the instrument and the differential item functioning (DIF) for sex, education and age. Results: The internal consistency of the HDKQ-BR was 0.694. The test-retest reliability was confirmed by the intraclass correlation coefficient (ICC = 0.779). According to the IRT, parameter a was between 0.176 and 1.175 and parameter b between −10.834 and 4.969. Discussion: The HDKQ-BR showed unidimensional structure and adequate psychometric performance for its application in populations with the same profile in Brazil. Translation to Health Education Practice: To assess the knowledge of an adult population about CVDs is important for improving the health literacy. The study focused on Area I of Responsibilities for Health Education Specialists (Assessment of Needs and Capacity).